Task-switching and long-term priming: Role of episodic stimulus–task bindings in task-shift costs - Waszak, Florian; Hommel, Bernhard; Allport, Alan (Cognitive psychology, 2003)
When subjects switch between two tasks, performance is slower after a task switch than after a task repetition. We report five experiments showing that a large part of these “task-shift-costs” cannot be attributed to a control operation, needed to configure the cognitive system for the upcoming task (e.g., Rogers & Monsell, 1995). In all experiments subjects switched between picture-naming and word-reading. We presented different stimuli either in just one of the two tasks, or in both of them. Shift-costs were larger for stimuli presented in both tasks than for those presented in only one task, even after more than 100 intervening trials between prime and probe events. We suggest (as proposed by Allport & Wylie, 2000) that stimuli acquire associations with the tasks in which they occur. When the current task activation is weak, as on a switch of tasks, stimuli can trigger retrieval of the associated, competing task, provoking larger time costs.